Characteristics of pulmonary tuberculosis in HIV seropositive and seronegative patients in a Northeastern region of Brazil - Liberato Isabella Ramos de Oliveira; Albuquerque Maria de Fatima P. Militão de; Campelo Antônio Roberto Leite; Melo Heloísa Ramos Lacerda de (Sociedade Brasileira de Medicina Tropical (SBMT), 2004)
The aim of this study was to analyse the clinical, epidemiological and bacteriological features present in 60 pulmonary tuberculosis patients who were also infected with human immunodeficiency virus (HIV) and to compare these with 120 TB patients who were not infected with HIV. The patients with pulmonary tuberculosis and HIV coinfection were mostly male (p = 0.001), showed a higher frequency of weight loss >10 kilos (p <0.001), had a higher rate of non-reaction result to the tuberculin skin test (p <0.001), a higher frequency of negative sputum smear examination for acid-fast bacilli (p = 0.001) and negative sputum culture for Mycobacterium tuberculosis (p = 0.001). Treatment failure was more common in those who were HIV positive (p <0.000). No higher frequency of resistance to antituberculosis drugs was found to be associated with TB/HIV coinfection (p = 0.407). Association between extrapulmonary and pulmonary tuberculosis was more frequent in those seropositive to HIV than those without HIV virus, 30% and 1.6% respectively. These findings showed a predominance of atypical clinical laboratory features in co-infected patients, and suggest that health care personnel should consider the possibility this diagnosis.